(3GdJMHjQ dEjVGM eYGfi GdJjSjQs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s; (3YHO GdQMef Hf Ydj Hf eMeO GdTjHGfqj GdRHjOj GdTGaYqj, hLjg GdOjf, GdeYQha H` GHf GdnqOrjnHY,J (B944 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fMeOg hfSJYjfg hHYO aEf gPG GdJMHjQ dEjVGM eYGfi GdJjSjQ bUOJ Hg EjVGM eG ajg hEXgGQ eG Nai ef eYGfjg s
(3BNQgG (B:s
(3bhdg ai MOjK GHf YHGS (B: (3Cgd GdfHi Udi Gddg Ydjg hBdg hSde HYeQI , Ci eVGaI Edi GdML aHGdChdi ef UGQJ MdGdkG hGddg CYde GfJgi hddg GdMeO s
(3hLGeY GdCUhd gh dCHj GdSYGOGJ eMeO Hf eMeO GHf GdCKjQ GdeJhai SfI (B606(3g`s
(3hYdi UOQ GdfSNI Jedc eDda GdcJGH hJedjcGJ CNQis
(3cJH eJf GdJjSjQ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs